Promoter methylation of MCAM, ERα and ERβ in serum of early stage prostate cancer patients - Brait, Mariana (Oncotarget, 2017)
BACKGROUND: Prostate cancer (PC) is the second most common cancer among men worldwide. Currently, the most common non-invasive approach for screening and risk assessment of PC is measuring the level of serum prostate-specific antigen (PSA). However, the sensitivity of PSA is 42.8 % and specificity is 41.1%. As a result, the serum PSA test leads to numerous unneeded biopsies. Therefore, a rigorous search for biomarkers for early detection of PC is ongoing. In this study, we aim to assess a panel of epigenetic markers in an intend to develop an early detection test for PC. RESULTS: The sensitivity and specificity of hypermethylation of MCAM was 66% and 73% respectively which is an improvement from the sensitivity and specificity of PSA. Considering a combination marker panel of MCAM, ERα and ERβ increased the sensitivity to 75% and the specificity became 70% for the minimally invasive early detection test of PC. MATERIALS AND METHODS: Sixteen primary matched tumor and serum were analyzed by quantitative methylation specific PCR (QMSP) to determine analytical and clinical sensitivity of the genes tested (SSBP2, MCAM, ERα, ERβ, APC, CCND2, MGMT, GSTP1, p16 and RARβ2). Additionally, serum samples from eighty four cases of PC, thirty controls and seven cases diagnosed as high grade Prostatic Intraepithelial Neoplasia (HGPIN) were analyzed. CONCLUSIONS: Promoter methylation of MCAM, ERα and ERβ have a potential to be utilized as biomarker for the early detection of prostate PC as their sensitivity and specificity seem to be better than serum PSA in our cohort of samples. After robust validation in a larger prospective cohort, our findings may reduce the numbers of unwarranted prostate biopsies.